1997
DOI: 10.1210/en.138.4.1520
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity of a Dieldrin/Toxaphene Mixture in the Mouse Uterus, MCF-7 Human Breast Cancer Cells, and Yeast-Based Estrogen Receptor Assays: No Apparent Synergism

Abstract: The estrogenic activity of dieldrin, toxaphene, and an equimolar mixture of both compounds (dieldrin/toxaphene) was investigated in the 21-day-old B6C3F1 mouse uterus, MCF-7 human breast cancer cells, and in yeast-based reporter gene assays. Treatment of the animals with 17beta-estradiol (E2) (0.0053 kg/day x3) resulted in a 3.1-, 4.8-, and 7.8-fold increase in uterine wet weight, peroxidase activity, and progesterone receptor binding, respectively. In contrast, treatment with 2.5, 15 and 60 micromol/kg (x3) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 0 publications
3
46
1
Order By: Relevance
“…The interactions of both potent and weak Ah receptor agonists to give nonadditive interactions has previously been reported from multiple laboratories and summarised in a recent review (Safe 1998). The non-additive antagonistic interactions between various PHAH are also consistent with results obtained for other ligand-induced transcription factors such as the estrogen receptor (ER) where PHAH such as PCB153: exhibit tissue specific weak ER aginist/antagonist activities (Ashby et al 1997;Gaido et al 1997;Ramamoorthy et al 1997). …”
Section: Resultssupporting
confidence: 52%
“…The interactions of both potent and weak Ah receptor agonists to give nonadditive interactions has previously been reported from multiple laboratories and summarised in a recent review (Safe 1998). The non-additive antagonistic interactions between various PHAH are also consistent with results obtained for other ligand-induced transcription factors such as the estrogen receptor (ER) where PHAH such as PCB153: exhibit tissue specific weak ER aginist/antagonist activities (Ashby et al 1997;Gaido et al 1997;Ramamoorthy et al 1997). …”
Section: Resultssupporting
confidence: 52%
“…Bioassay based on biomarker is promising due to its molecular and biological simplicity, easy handling, and low costs (Ramamoorthy et al 1997). In addition, this assay is valuable because it is able to indicate a potential mechanism of action as well as to account for synergistic, antagonistic, and additive interactions that may occur with a complex mixture.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37] Assays determining ER binding or transactivation are useful but do not predict SERM-like activity, and our results actually support, in part, the EDC hypothesis where it can be hypothesized that a so-called 'weak' estrogen such as BPA may be more potent in some tissues during specific periods of development. In collaboration with Drs Kevin Gaido (Chemical Industry Institute of Toxicology), Donald McDonnell (Duke University) and Ken Korach (National Institutes for Environmental Health Sciences), we also showed that interactions of several environmental estrogens were additive 38,39 and this refuted a paper in Science claiming 'synergistic' interactions of environmental estrogens. 40 This discovery of synergistic activity for some estrogenic EDCs was covered by the news media worldwide; however, our results and the subsequent retraction of the Science paper were barely mentioned in the press.…”
Section: Involvement In the Edc Controversiesmentioning
confidence: 61%